2019
DOI: 10.1093/cid/ciz303
|View full text |Cite
|
Sign up to set email alerts
|

Rates of New Human Immunodeficiency Virus (HIV) Diagnoses After Reported Sexually Transmitted Infection in Women in Louisiana, 2000–2015: Implications for HIV Prevention

Abstract: Background Human immunodeficiency virus (HIV) prevention interventions for prevention interventions for women include screening, partner notification, promoting condoms, and preexposure prophylaxis (PrEP). Women’s risk of acquiring HIV can help guide recommendations. Methods We used data from Louisiana’s sexually transmitted infection (STI) and HIV registries to study 13- to 59-year-old women following first diagnosis of syph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Gonorrhoea infection in women was associated with a significantly increased risk of HIV seroconversion. Three studies were included [ 40 , 51 , 52 ], one in sex workers [ 40 ], and all three reported an increased risk. Data from the two large studies using a general-population sample were pooled.…”
Section: Resultsmentioning
confidence: 99%
“…Gonorrhoea infection in women was associated with a significantly increased risk of HIV seroconversion. Three studies were included [ 40 , 51 , 52 ], one in sex workers [ 40 ], and all three reported an increased risk. Data from the two large studies using a general-population sample were pooled.…”
Section: Resultsmentioning
confidence: 99%
“…There are dire consequences to this lack of awareness; other studies are beginning to quantify the number of new HIV diagnoses that could be prevented among women had they only been provided with PrEP at the time key risk factors (such as STI diagnoses) were realized. 23 Efforts to promote PrEP to women are needed, especially in Fulton County, so the results of this study not only get us closer to identifying women at greatest risk of HIV but also quantify that increased risk. This quantification would allow clinicians to tell female patients how much more likely they are to acquire HIV because of certain risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…19,21,22 For example, a study conducted in Louisiana found that women with an STI were diagnosed with HIV at a rate 2.3 times that of women without an STI. 23 While risk factors for HIV among men who have sex with men (MSM) have been well-characterized in various settings and locations across the United States, less is known about the impact these factors have for HIV acquisition among women specifically in urban, low-income Southern US settings. 8 Despite the high HIV burden among minority women, very few epidemiologic studies have assessed risk factors for HIV among black women in the United States, and more specifically among black women within HIV ''hotspots'' in the South.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, casual sex may be one of the notable perceived Australian sexual scripts that may have serious implications for HIV and STI transmission. Though the risk of HIV transmission may be low in Australia, STI prevalence is relatively high and also on the increase [ 41 , 42 ] and infection with an STI can increase the risk of HIV [ 43 ]. According to the study findings, participants believe that premarital sex in Australia is mostly casual, compared to their home countries; where it is supposed to occur in a romantic relationship that may lead to marriage.…”
Section: Discussion Of Findingsmentioning
confidence: 99%